Level of Son Students' Futsal Playing Skills in Extracurricular at SMAN 2 Batang - Aryo Prakosa; Pungki Indarto (UNIB Press, 2022)
Sports exercises combine several ways to maintain actual health so that they can be relied upon in an acceptable situation. Futsal is a practical game like in a soccer game carried out by two playgroups and with the struggle for the ball carried out between the players along with the determination to place the ball that is herded into the opponent's goal and doing the barrier so as not to release the ball. This research was conducted with the aim of knowing the level of futsal playing skills of male students who participated in extracurricular activities at SMA N 2 Batang. This study uses quantitative research with survey and testing methods. The results showed that the highest passing control skills were in an adequate category for 9 students (45%). The skill of dribbling gets the highest results in the good category of 9 students (45%). Shooting skills get the highest results in sufficient categories of 7 students (35%). It can be concluded that the level of futsal skills of male students in extracurricular activities in SMA N 2 Batang is for the level of graduation control skills (less), then the level of dribbling skills (good), and for shooting skills (enough).